Public Service Management in Stunting Prevention: Evaluation of Service Quality, Responsiveness, and Effectiveness in Jeneponto Regency - Muhammad Luthfi Siraj; Wilfred Uronu Lameck; Ismail; Suprianto (Faculty of Social and Political Sciences Universitas Prof Dr Hazairin, SH, 2026)
This study analyzes public service management in stunting prevention in Jeneponto Regency, Indonesia, focusing on service quality, responsiveness, and effectiveness. A qualitative case study approach was employed involving 15 informants, including local government officials, health workers, community leaders, and program beneficiaries. Data were collected through in-depth interviews, observations, and document analysis, then analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing. The findings reveal that service quality remains uneven due to limited health infrastructure, shortages of nutritionists, and inconsistent service delivery across villages. Responsiveness is constrained by delayed complaint handling, limited adaptation to local socio-cultural conditions, and low community participation. Although stunting prevalence declined from 37.4% in 2021 to 30.3% in 2023, program effectiveness remains suboptimal because coordination, monitoring, and targeting mechanisms are not fully optimized. This study highlights the interconnection between service quality, responsiveness, and effectiveness in evaluating local public service management for sustainable stunting reduction.